2012
DOI: 10.3382/ps.2012-02300
|View full text |Cite
|
Sign up to set email alerts
|

Noncaged laying hens remain unflappable while wearing body-mounted sensors: Levels of agonistic behaviors remain unchanged and resource use is not reduced after habituation

Abstract: Unique markings or body-mounted sensors facilitate data collection from individuals in large groups of similar-looking conspecifics but may have unintended consequences on behavior. A wireless sensor attached to the back of laying hens via a harness has been developed to monitor space use and activity. Prior to collecting experimental data, effects of the sensor on resource use and social interactions were assessed. Four rooms of 135 hens each were weighed and 10 hens/room were randomly fitted with sensors at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…Furthermore, the availability of an IR camera in a housing system could be useful also for other purposes. Up to day, thermographic image analysis of poultry has proven to improve the welfare of these animals [19,20,22]. For example, Yahav et al [33] evaluated data from an IR camera in order to measure the body surface temperature of chickens as a basis for calculating heat loss by radiation and convection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the availability of an IR camera in a housing system could be useful also for other purposes. Up to day, thermographic image analysis of poultry has proven to improve the welfare of these animals [19,20,22]. For example, Yahav et al [33] evaluated data from an IR camera in order to measure the body surface temperature of chickens as a basis for calculating heat loss by radiation and convection.…”
Section: Discussionmentioning
confidence: 99%
“…Another technology that has been tested to automatically detect laying hens is based on sensors that allow the building of a geographic information system (GIS) [21,22,23]. These sensors have to be worn by hens.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor harnesses were fitted to the hens 3 wk prior (at 26 wk) to the training phase to allow for ha- bituation (Daigle et al, 2012), and remained on the hens throughout the entire training and data collection period. Hens were habituated to the handler by holding each hen individually within her home pen for a period of 30 to 60 s, beginning with 30 s the first day and increasing at 10-s increments until 60 s was reached.…”
Section: Hen Training Proceduresmentioning
confidence: 99%
“…The hens were individually marked with numbered PVC plates (8 × 6 cm) mounted on the back of the hens with two straps that went under the wings (as in Harlander Matauschek et al, 2010). Daigle et al (2012) studied the behaviour of hens outfitted with similarly mounted sensors and found that aggressive interactions were not affected and that the hens habituated to the tags within two weeks in terms of resource use.…”
Section: Animals Housing and Treatmentsmentioning
confidence: 99%